Impairment of endothelium-dependent vasodilator function of retinal blood vessels in adult rats with a history of retinopathy of prematurity - Asami Mori; Daiki Sumida; Ryo Kondo; Ayuki Nakano; Shiho Arima; Daiki Asano; Akane Morita; Kenji Sakamoto; Tohru Nagamitsu; Tsutomu Nakahara (Elsevier, 2021)
Retinopathy of prematurity (ROP) is a proliferative retinal vascular disease, initiated by delayed retinal vascular growth after premature birth. In the majority of cases, ROP resolves spontaneously; however, a history of ROP may increase the risk of long-term visual problems. In this study, we evaluated the endothelial function of retinal blood vessels in adult rats with a history of ROP. ROP was induced in rats by subcutaneous injection of a vascular endothelial growth factor receptor tyrosine kinase inhibitor (KRN633) on postnatal day (P) 7 and P8. On P56, vasodilator responses to acetylcholine, GSK1016790A (an activator of transient receptor potential vanilloid 4 channels), NOR3 (a nitric oxide [NO] donor), and salbutamol (a β2-adrenoceptor agonist) were assessed. Compared to age-matched controls, retinal vasodilator responses to acetylcholine and GSK1016790A were attenuated in P56 rats with a history of ROP. No attenuation of acetylcholine-induced retinal vasodilator response was observed under inhibition of NO synthase. Retinal vasodilator responses to NOR3 and salbutamol were unaffected. These results suggest that the production of and/or release of NO is impaired in retinal blood vessels in adult rats with a history of ROP. A history of ROP might increase the risk of impaired retinal circulation in adulthood.